“Ready for Landing”—study protocol for the evaluation of a brief sleep hygiene group intervention for youth with psychiatric disorders - Meyer, Paula Theresa; Brauer, Hannah; Schreiber, Clara Marie; Heinze, Pia Muriel; Witte, Julia; Berger, Christoph; Munz, Manuel; Dück, Alexander; Reis, Olaf; Kölch, Michael; Prehn-Kristensen, Alexander (Frontiers in Psychology, 2025)
BackgroundMany children and adolescents with psychiatric disorders struggle with sleep problems that oftentimes stay unaddressed in therapeutic settings due to limited resources. Still, there is evidence that improving insufficient sleep positively affects mental health recovery. Addressing an adequate sleep hygiene is named to be the first line of treatment when it comes to unspecific sleep problems. The present study aims to evaluate the efficacy of a brief sleep hygiene group intervention for children and adolescents with psychiatric disorders named “Ready for Landing.” The intervention is designed to improve sleep quality and elongate sleep duration by explaining the process of falling asleep using the metaphor of an airplane landing. Elements of psychoeducation and cognitive behavioral therapy for insomnia are combined.MethodThe study plans to investigate the efficacy of the intervention using a waitlist control design. A sample of children and adolescents (aged 10–18 years) that are undergoing treatment for psychiatric disorders in day treatment centers in Kiel and Rostock, Germany, will be included. Sleep quality is assessed using the Pittsburgh Sleep Quality Index. Sleep duration is assessed by using a sleep diary completed by the patients and as well using actigraphy as an objective measure. Analysis of variance will be used to detect treatment effects. Secondary outcomes include variables regarding sleepiness.DiscussionIf “Ready for Landing” proves to be efficacious the intervention has the potential to bridge the gap between frequent sleep problems in youth with mental health problems and limited resources to target those. Serving as an effective and economic tool, it could support mental healthcare professionals. It is a promising intervention to support the positive outcome of mental health treatments by improving sleep in children and adolescents.Clinical trial registrationhttps://www.bfarm.de/DE/Das-BfArM/Aufgaben/Deutsches-Register-Klinischer-Studien/_node.html, identifier DRKS00034984.